PREDICTION OF WAVE RUNUP HEIGHT AGAINST COASTAL PROTECTION AT ANYER BEACH, SERANG REGENCY USING ANN METHOD - Nadeak, Novintasari
Wave run-up is a critical factor that influences coastal flooding, shoreline changes, and damage to coastal structures. Climate effects also impact wave run-up in coastal areas. Therefore, efficient and accurate prediction of wave run-up is crucial for effective coastal engineering design and management. Predicting wave run-up can be time-consuming due to the influence of nonlinearity and nonstationarity processes. Hence, this study utilizes a Machine Learning (ML) approach, specifically an Artificial Neural Network (ANN) trained with the backpropagation algorithm, to predict wave run-up. Numerical modeling will also be employed to understand wave run-up dynamics on the coast using Delft3D Flow+Wave and XBeach. This methodology will combine the computational efficiency of the XBeach numerical model with ANN as its predictor.